Updating the Relationship Between the Threshold Value of Average Nucleotide Identity and Digital DNA–DNA Hybridization for Reliable Taxonomy of Corynebacterium - Haitham Elbir (Veterinary Sciences)
Currently, bacterial classification at the species level relies on the 95–96% average nucleotide identity (ANI) value that is known to be equivalent to a 70% digital DNA–DNA hybridization (dDDH) value. However, during the routine identification of bacteria in the uteri of camels with a history of conception failure, we found that four out of the seven strains (2298A, 2569A, 2652, 2571B, 1103A, 2571A, and 335C) could not be assigned to any valid Corynebacterium species. Furthermore, a 70% dDDH value did not correspond to a 95–96% ANI value in strain 2569A. Thus, we aimed to classify these strains and explain the mechanisms underlying gene repertoire diversity and the disagreement we found between the ANI and dDDH cutoff values. For this study, we extracted information from the genomes of 150 Corynebacterium-type species and seven sequenced genomes of uterine Corynebacterium isolates. We found that the 96.67% OrthoANI value should be used in place of the generally accepted 95–96% ANI threshold in order to obtain an equivalent 70% dDDH value. Phylogenomic analysis determined the evolutionary position of each uterine strain. Then, strains 2652 and 2571B were classified as C. camporealensis based on the ANI value (98.44% and 98.72%) and dDDH value (85.8% and 88.5%). Strain 2569A had a 96.58% ANI and a 69.4% dDDH value and was classified as C. urogenitale. The strains 335C, 1103A, 2571A, and 2298A were classified as novel Corynebacterium based on the ANI value (77.12, 94.01%, 94.26%, and 94.03%) and dDDH value (21.3%, 54.1%, 54.9%, and 51.3%), respectively. Genes for menaquinone biosynthesis and the saturation of chains were detected in uterine strains and their closely related type strains. Gene gain predominates as a source of variation in the gene repertoire. Most of these genes are gained by horizontal gene transfer, driven by genomic islands and prophage. In summary, we refined the ANI cutoff value for an accurate diagnosis of Corynebacterium. Moreover, we clarified the mechanism underlying the diversity of the gene repertoire and expanded the number of Corynebacterium species isolated from the camel uterus.